Strategic negotiation in multiagent environments - Kraus, Sarit (Intelligent robots and autonomous agents., 2001)
"As computers advance from isolated workstations to linked elements in complex communities of systems and people, cooperation and coordination via intelligent agents become increasingly important. Examples of such communities include the Internet, electronic commerce, health institutions, electricity networks, and digital libraries. Sarit Kraus is concerned here with the cooperation and coordination of intelligent agents that are self-interested and usually owned by different individuals or organizations. Conflicts frequently arise, and negotiation is one of the main mechanisms for reaching agreement. Kraus presents a strategic-negotiation model that enables autonomous agents to reach mutually beneficial agreements efficiently in complex environments. The model, which integrates game theory, economic techniques, and heuristic methods of artificial intelligence, can be automated in computer systems or applied to human situations. The book provides both theoretical and experimental results."